Ethnomathematics approach ofmathematics’s professor profile, in theindigenousschools, oftheRio Grande do Sul Northwest region - Domênico, Camila Nicola Boeri Di; Piovesan, Caliandra (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
It is known that the vision of mathematics taught in indian villages is different from taught in mainstream schools. In this sense, the ethnomathematics’s work in the dialogue with indigenous peoples, isto do valorize their culture increasingly, recognizing their constructions and their cultural productions and avoiding conflicts that result from the introduction of the ’math’s white’ in indigenous education. Thus, this article aims to characterize the process of teaching and learning of mathematics, in the indigenous education of the various reserves in the northwestern region of the state of Rio Grande do Sul, from the perspective of ethnomathematics, highlighting the profile of the teacher. Interviewswith six math teachers of Indian schools of Iraí, LiberatoSalzano and Planaltowere performed. Many are the difficulties encountered in mathematics education in indigenous schools and, when questioned, teachers reported many. Besidesthe contents, other difficulties were highlighted as media influence, lack of concentration of students with discipline and dislike of Math. Highlights the importance of this research to the wider community, where one starts to have knowledge about the professional life of mathematics teachers in Indian schools, as well as in relation to the profile of this professional.